Linking aberrant glycosylation of plasma glycoproteins with progression of myelodysplastic syndromes: a study based on plasmonic biosensor and lectin array - Chrastinová, Leona; Pastva, Ondřej; Bocková, Markéta; Kovářová, Hana; Ceznerová, Eliška; Kotlín, Roman; Pecherková, Pavla; Štikarová, Jana; Hlaváčková, Alžběta; Havlíček, Marek; Válka, Jan; Homola, Jiří; et al. (Scientific reports, 2023)
Aberrant glycosylation of glycoproteins has been linked with various pathologies. Therefore, understanding the relationship between aberrant glycosylation patterns and the onset and progression of the disease is an important research goal that may provide insights into cancer diagnosis and new therapy development. In this study, we use a surface plasmon resonance imaging biosensor and a lectin array to investigate aberrant glycosylation patterns associated with oncohematological disease-myelodysplastic syndromes (MDS). In particular, we detected the interaction between the lectins and glycoproteins present in the blood plasma of patients (three MDS subgroups with different risks of progression to acute myeloid leukemia (AML) and AML patients) and healthy controls. The interaction with lectins from Aleuria aurantia (AAL) and Erythrina cristagalli was more pronounced for plasma samples of the MDS and AML patients, and there was a significant difference between the sensor response to the interaction of AAL with blood plasma from low and medium-risk MDS patients and healthy controls. Our data also suggest that progression from MDS to AML is accompanied by sialylation of glycoproteins and increased levels of truncated O-glycans and that the number of lectins that allow discriminating different stages of disease increases as the disease progresses.
Keywords: myelodysplastické syndromy; krevní plazma; Leukemia, Myeloid, Acute; Myelodysplastic Syndromes; glykoproteiny; Lectins; lektiny; glykosylace; Humans; lidé; Glycosylation; Glycoproteins; Plasma; biosenzitivní techniky; akutní myeloidní leukemie; Biosensing Techniques